Evaluation of the Therapeutic Effect of Adjuvant Transcatheter Arterial Chemoembolization Based on Ki67 After Hepatocellular Carcinoma Surgery - Yu-Fei Zhao; Xiu Xiong; Kai Chen; Wei Tang; Xu Yang; Zheng-Rong Shi (Frontiers in Oncology, 2021)
Background and aimsThis study aimed to determine the relationship between Ki67 expression and the efficacy of postoperative adjuvant transcatheter arterial chemoembolization (PA-TACE) in patients with hepatocellular carcinoma.MethodsThe Kaplan-Meier method was used to analyze the recurrence-free survival (RFS) and overall survival (OS) rates between the sub-groups in the ki67 low expression group and the ki67 high expression group and analyze the relationship between the expression of Ki67 and the efficacy of TACE.ResultsAfter PSM, there was no significant difference in the RFS and OS between the surgery + TACE and surgery subgroups after 1, 2, or 3 years (RFS: 63.9%, 55.6%, and 42.9% vs. 83.3%, 63.9%, and 55.6%, respectively, P = 0.279; OS: 91.7%, 83.3%, and 74.3% vs. 91.7%, 88.9%, and 71.4%, respectively, P = 0.890) in the Ki67 low-expression group. The RFS and OS were higher in the surgery + TACE subgroup than the surgery subgroup after 1, 2, and 3 years (RFS: 80.0%, 77.5%, and 69.2% vs. 53.5%, 39.5%, and 32.6%, respectively, P<0.001; OS: 97.5%, 85.0%, and 79.5% vs. 79.1%, 48.8%, and 42.9%, respectively, P = 0.001) in the Ki67 high expression group. The RFS was higher in the Ki67 high-expression subgroup than the low-expression subgroup after 1, 2, and 3 years, and OS had no significant difference (RFS: 80.0%, 79.5%, and 69.2% vs. 67.4%, 56.5%, and 46.7%, respectively, P = 0.035; OS: 97.5%, 85.0%, and 79.5% vs. 93.5%, 82.6%, and 75.6%, respectively, P = 0.665) in the surgery + TACE group.ConclusionsFor patients with hepatocellular carcinoma and high expression of Ki67 (Ki67≥20%), adjuvant hepatic artery chemoembolization after radical liver tumor resection effectively reduced the probability of tumor recurrence after surgery and prolonged the OS of patients. High Ki67 expression during the post-operative follow-up evaluation of hepatocellular carcinoma patients is an indicator for adjuvant TACE therapy.